Morphology Transformations of Platelets on Plasma Activated Surfaces. Issue 6 (9th April 2014) - Modic, Martina; Junkar, Ita; Stana‐Kleinschek, Karin; Kostanjšek, Rok; Mozetič, Miran
<x xml:space="preserve">Abstract</x> Improved hemocompatibility from the perspective of platelets adhesion and activation on polyethylene terephthalate surfaces has been addressed. The activation stage of platelets has been determined from their size and morphology using scanning electron microscopy (SEM). The activation of platelets on untreated polymer materials was very intensive. Polymer materials were treated with weakly ionized oxygen plasma in order to repel platelet adhesion. Already short treatment times (3s) showed significant reduction of the total number and of highly activated forms of adhered platelets. Possible mechanisms of different behaviour of blood platelets on plasma treated polymer were discussed in terms of surface adhesion and changes in morphology.<inline-graphic xlink:href="ark:/27927/pghmhk0nvb" content-type="ppap201400001-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />